The Death of Orpheus in a Poem of Los placeres prohibidos (Minerva, 2017)
Luis Cernuda reproduced his own death in the arms of his lover, probably the adolescent rent boy Serafín Fernández Ferro, in one of the poems of Los placeres prohibidos. The author has based that type of death on Orpheus’ in the different versions by Phanocles of Alexandria, Virgil and Ovid, in addition to later tradition. On choosing the musician of Thrace as a model, he confirms his fondness for adolescent boys, of around the same age as Serafín and his stormy relation with the beautiful Calais, the son of the wind. Thus, he establishes some parallelisms between his lover and Orpheus’ lover: his winged nature (by describing him as an “angel” and “archangel” in other works), and his youth and beauty. Cernuda might have read the Greek poem by Fanocles in the Latin version by Nicolaus Bach (Halle 1829) or, more likely, in the Italian rendering by Luigi Lamberti (Venice 1842).
Keywords: Phanocles of Alexandria; Virgil; Ovid; homosexual Orpheus; Luis Cernuda